Effectiveness of student responsibility instruments in design basic learning process - Denok Ayu Lestari; Ismet Basuki; Meini Sondang (Jurnal Taman Vokasi, 2019)
The aim of this research is to describe the responsibilities of students in basic designlearning at Boutique Fashion Departement at SMK Negeri 3 Blitar. To support this study, we use aqualitative survey method approach to 32 students of class X. The result shows that there are severalfactors that influence student’s attitudes, namely student participation, respect for others, cooperation,leading, and expressing opinions. The results of the questionnaire show that most students feelresponsible for respecting others with excellent criteria, while students feel responsibility forparticipating, working together, leading and expressing opinions on good criteria. The result of theobservations shows that